Effect of Liming on Soil Properties, Nutrient Content and Yield of Wetland Rice in Acid Tropical Soils of Kerala - P. S, Bhindhu; P., Sureshkumar; Abraham, Mini; Kurien, E. K. (International Journal of Bio-resource and Stress Management, 2018)
The acid tropical soils of Kerala are characterized with low levels of basic cations and high levels of acidic cations like iron and manganese. Rice grown under flooded conditions are associated with high concentration of iron in the rhizosphere due to reduced soil environment. Higher iron content in the rhizosphere has antagonistic effect on uptake of essential nutrients leading to reduction of yield. An experiment was conducted in the first crop season of 2015 to study the influence of lime application on soil properties, plant nutrient content and yield of rice. The treatments included three sources of lime viz. calcium oxide, calcium carbonate and dolomite applied in three doses viz. as per POP recommendation, as per ΔpH and as per lime requirement based on SMP buffer method and a control with no lime application. Application of calcium carbonate as per lime requirement based on SMP buffer method increased the soil pH from 4.90 to 7.10 at harvest of the crop when compared to 4.85 in the control plot. Lime applied as per lime requirement based on SMP buffer method increased the availability of potassium, calcium, sulphur and reduced the levels of available iron, manganese, copper and zinc. Content of potassium, calcium and sulphur in plant increased with dose of lime applied while the plant content of magnesium, iron, manganese, zinc and copper decreased. Application of dolomite increased the available magnesium in soil and the magnesium content in plant. Dolomite applied as per ΔpH was found to be the optimum dose in increasing the yield of rice.